Análisis del desempeño de la ceniza de cascarilla de arroz como sustituto parcial del cemento hidráulico en el concreto - Calderón-Solano, Diego Esteban (Instituto Tecnológico de Costa Rica, 2022)
In this study, the performance of rice husk ash as partial replacement of hydraulic cement in concrete is analyzed. This extends from the need of the Nacional Rice Corporation (Conarroz) of finding possible uses to this by-product obtained from de rice plant during harvest. The rice husk ash content replacement defined for the concrete mixes were 10, 20 and 30%; and Conarroz provided rice husk ash from three different harvests. Nine concrete mix designs were made contemplating all the possible combinations of rice husk ash and content replacements and one concrete mix design was made for the regular concrete. In total, 45 concrete specimens were made per concrete mix, which were tested at the ages of 7, 14 and 28 days to determine the compressive strength of the concretes. The results were corroborated by a statistical analysis which helped identify possible sources of variation. The results showed that the rice husk ash has a negative impact in the development of the compressive strength of concrete, and none of the concrete mixes made with rice husk ash surpassed the compressive strength of the regular concrete reached at the 28-day mark.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2022
Keywords: Ceniza -- Cascarilla de arroz; Cemento portland; Materiales cementicios; Concreto; Diseño de mezcla del concreto; Resistencia de materiales; Ash -- Rice husk; Portland cement; Cementitious materials; Concrete mix design; Material resistance; Strength of materials; Research Subject Categories::TECHNOLOGY::Engineering mechanics::Construction engineering; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture::Other civil engineering and architecture